High-Frequency Isolated Bidirectional Dual Active Bridge DC-DC Converters with Wide Voltage Gain - Sha, Deshang; Xu, Guo.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Written by experts, this book is based on recent research findings in high- frequency isolated bidirectional DC-DC converters with wide voltage range. It presents advanced power control methods and new isolated bidirectional DC-DC topologies to improve the performance of isolated bidirectional converters. Providing valuable insights, advanced methods and practical design guides on the DC-DC conversion that can be considered in applications such as microgrid, bidirectional EV chargers, and solid state transformers, it is a valuable resource for researchers, scientists, and engineers in the field of isolated bidirectional DC-DC converters.
Introduction -- Simplified and Unified Control for Voltage Fed Dual Active Bridge Converter -- Hybrid-Bridge-Based Voltage Fed Dual Active Bridge Converter -- Dual-Transformer-Based Voltage Fed Dual Active Bridge Converter -- Blocking-Capacitor-Based Voltage Fed Dual Active Bridge Converter -- Three-level Bidirectional DC-DC Converter with an Auxiliary Inductor for Full-Operation Zero-Voltage Switching -- Current-Fed Dual Active Bridge DC-DC Converter with Dual PWM plus Double Phase Shifted Control---Identical Duty Cycle Control -- Current-fed Dual Active Bridge Converter Using Optimized Switching Patterns---Un-identical Duty Cycle Control -- Half Bridge Three-Level Current-Fed Dual Active Bridge Converter with Direct Slew Rate Control---Identical Duty Cycle Control -- Full Bridge Three-Level Current-Fed Dual Active Bridge Converter with Identical Duty Cycle Control -- Current-fed Hybrid Dual Active Bridge Converter -- Future Work.
Keywords: Electric power production; Electronic circuits; Renewable energy sources; Electrical Power Engineering; Electronic Circuits and Systems; Renewable Energy; Mechanical Power Engineering